Effect of Green, Tulsi, and Areca Teas on the Color Stability of Two Composite Resin Materials – an in vitro Spectrophotometric Analysis - Patil A; Muliya VS; Pentapati KC; Kamath S (Dove Medical Press, 2020)
Akshata Patil,1 Vidya-Saraswathi Muliya,1 Kalyana-Chakravarthy Pentapati,2 Shobha Kamath3 1Department of Conservative Dentistry and Endodontics, Manipal College of Dental Sciences, Manipal, Manipal Academy of Higher Education, Manipal, Karnataka, India; 2Department of Public Health Dentistry, Manipal College of Dental Sciences, Manipal, Manipal Academy of Higher Education, Manipal, Karnataka, India; 3Department of Biochemistry, Kasturba Medical College, Manipal, Manipal Academy of Higher Education, Manipal, Karnataka, IndiaCorrespondence: Vidya-Saraswathi MuliyaDepartment of Conservative Dentistry and Endodontics, Manipal College of Dental Sciences, Manipal, Manipal Academy of Higher Education, Manipal 576 104, Karnataka, IndiaTel +91-984-574-2360Email vidya.saraswathi@manipal.eduObjective: To compare the effect of Green, Tulsi, and Areca teas on the color stability of two composite materials on the 30th and 60th days.Materials and Methods: Two light cure composite restorative materials, Brilliant EverGlow (Group 1) and Brilliant NG, (Group 2) with different resin and filler characteristics were selected. The test solutions selected were Green tea, Tulsi tea, Areca tea, and artificial saliva (control group). In total, 104-disc shaped specimens were fabricated using a custom made brass mold as per the manufacturer instructions. All specimens were put in storage for rehydration and complete polymerization at 37°C in distilled water for 24 hours. Specimens of each composite material were randomly divided into four subgroups of 13 samples. Tea solutions were freshly prepared, and specimens were immersed in the respective solutions every day for 15 minutes for 60 days. Specimens were stored in artificial saliva after the immersion regimen. The color evaluation was done before immersion, on the 30th and 60th day, using a digital reflectance spectrophotometer.Results: At 30 days, Group 1 specimens immersed in Areca and Green teas showed significantly higher mean values than those in control and Tulsi tea. At 60 days in Group 1, specimens in Areca tea showed significantly higher mean value, followed by Green tea, Tulsi tea, and control. At 30 and 60 days in group 2, specimens in control had significantly lower mean values than other tea preparations. Group 1 showed a higher mean difference in ΔE than Group 2 specimens immersed in Green and Areca teas at 30 days (P=0.001 and 0.001) and 60 days (P=0.001 and < 0.001), respectively.Conclusion: All herbal tea preparations exhibited staining potential, which increased over time, and Areca tea showed the highest staining potential. Understanding the staining potential of newer tea preparations on recent composite materials helps the clinician to choose the right restorative materials.Keywords: Areca tea, composites, discoloration, green tea, stain, tulsi tea